Electrooculographic and Electroretinographic Changes among Patients Undergoing Treatment with Amiodarone - Tajik, Fatemeh; Shushtarian, Seyed Mohammad Masoud (Journal of Ophthalmic and Optometric Sciences, 2018)
Purpose: To evaluate the probable toxic effects of amiodarone on retina, using electrooculography (EOG) and electroretinography (ERG) testing methods. Patients and Methods: Fifty participants in the present study included 25 patients with a history of amiodarone treatment as the case group and 25 age, sex and visual acuity matched healthy volunteers with healthy visual system as the control group. All the participants underwent EOG and ERG examinations on their both eyes. The results obtained in two groups were compared to look for possible changes among patients undergoing treatment with amiodarone compared to the control group. Results: There was no statistically significant difference between the case and control groups regarding the age, sex, and visual acuity. Out of 50 eyes in the case group 9 eyes showed abnormal ERG including 7 eyes showing abnormal b-wave peak latency and 5 eyes showing abnormal b-wave peak amplitude. Three eyes had both abnormal latency and amplitude. In comparison, only one eye in the control group showed abnormal latency. The difference between the two groups in number of participants showing abnormal b-wave peak latency (P = 0.022) or amplitude (P = 0.027) were both statistically significant. Regarding the EOG testing 15 eyes among patients and 10 eyes from controls showed abnormal EOG Arden index indicating no statistically significant difference (P = 248). Conclusion: Based on the results of the present study we can conclude that amiodarone has toxic effects on retina, which might be detected and followed using ERG b-wave latency and amplitude. Keywords: Amiodarone; Retina; Electrooculography; Electroretinography.